2002
DOI: 10.1248/bpb.25.492
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Lipid Emulsion on an Injectable Formulation of Lipophilic KW-3902, a Newly Synthesized Adenosine A1-Receptor Antagonist.

Abstract: Several approaches to obtaining parenteral formulations for water-insoluble or poorly soluble drugs have been reported and dispersed systems for drug delivery such as emulsions, liposomes and nanospheres are improving all the time.1-12) For instance, diazepam recently became commercially available in a lipid emulsion form, 13,14) which was developed to reduce the incidence of local side effects after intravenous injection of conventional preparations of diazepam containing organic solvents. 7 ]nonyl)-3,7-dihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…36) A denser fraction detected in the density range of 1.006-1.063 g/ml corresponds to liposomes or liposome-like vesicles, according to the result of lipo-KW-3902 mentioned below. As we reported in the previous paper, 29) em-KW-3902 showed the KW-3902 distribution in which 78.8% was in the fraction of dϽ1.006 g/ml and 21.2% in 1.006-1.063 g/ml, corresponding to liposomes or liposome-like vesicles. In the case of lipo-KW-3902, 100% of KW-3902 was detected in the density range of 1.006-1.063 g/ml.…”
Section: Fractionation Of Kw-3902 In the Formulationssupporting
confidence: 79%
See 2 more Smart Citations
“…36) A denser fraction detected in the density range of 1.006-1.063 g/ml corresponds to liposomes or liposome-like vesicles, according to the result of lipo-KW-3902 mentioned below. As we reported in the previous paper, 29) em-KW-3902 showed the KW-3902 distribution in which 78.8% was in the fraction of dϽ1.006 g/ml and 21.2% in 1.006-1.063 g/ml, corresponding to liposomes or liposome-like vesicles. In the case of lipo-KW-3902, 100% of KW-3902 was detected in the density range of 1.006-1.063 g/ml.…”
Section: Fractionation Of Kw-3902 In the Formulationssupporting
confidence: 79%
“…We previously 29) investigated the influence of the emulsion formulation on the pharmacokinetics of KW-3902 using three different formulations: a lipid emulsion, a liposome and a saline solution, and found no significant difference in the pharmacokinetic parameters of the compound after injection of any of the formulations in rats. This confirmed that the lipid emulsions or the liposome formulations does not influence the intrinsic pharmacokinetics of KW-3902 and these formulations were defined as a solvent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the development of intravenously (IV) injectable formulations for KW3902, which has a solubility in water of <1 μg mL −1 , Hosokawa et al (2002) investigated the effects of a lipid emulsion and liposome formulation on the pharmacokinetics of KW3902 and its metabolite (M1-KW3902) in comparison to a 1 N NaOH-DMSO-containing formulation (Fig. 3).…”
Section: Animal Studiesmentioning
confidence: 99%
“…These studies demonstrate that emulsions may or may not have a significant impact on the distribution and elimination of drugs. Several molecules formulated as emulsions have exhibited pharmacokinetic parameters similar to that of a solution dosage form (107)(108)(109)(110)(111)(112). One of the main reasons for not observing any difference has been attributed to a rapid release of the drug from the emulsion.…”
Section: Pharmacokinetics and Tissue Distributionmentioning
confidence: 99%